Implementasi Teknologi Pembelajaran Melalui Aplikasi Canva Terhadap Peningkatan Motivasi Belajar Pada Mata Pelajaran Al-Qur’an Hadits Kelas V MI NW Aikmel - Alwan , Muhammad; Herawati , Nita Sunarya; Jusridawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to determine the effect of using the Canva application as a learning medium on increasing students' learning motivation. The background of this study is based on the low learning motivation of students in participating in conventional learning, which is less interesting. Learning innovation by utilizing digital media such as Canva is expected to create a more interactive and enjoyable learning atmosphere. The research method used is Classroom Action Research (PTK) conducted in two cycles. The research subjects are 10 fifth-grade students of MI NW Aikmel. Data collection techniques were carried out through observation, learning motivation questionnaires, and documentation. Data analysis was conducted descriptively and quantitatively to determine changes in student motivation levels before and after using the Canva application. The results of the study showed an increase in students' learning motivation after the implementation of the Canva application. In the preliminary action, the average percentage of students' learning motivation reached 49% (low category), and in cycle I it increased to 59% (medium category) and further increased in cycle II to 78% (very high category). These findings indicate that the use of the Canva application as a learning medium can significantly increase students' learning motivation.